Perkecambahan Biji Sawi (Brassica juncea (L.) Czern.) Varietas Tosakan yang Kedaluwarsa Berdasarkan Bahan Priming dan Lama Waktu Perendaman - Suci Hikmatul Haq; Dwi Gusmalawati; Siti Ifadatin (Universitas Islam Raden Rahmat, Malang, 2024)
This study aims to determine the morphology of seed embryos, sprout development, and germination components. The research design was RAL based on priming materials and soaking time. Each treatment consisted of four replicates. Data were analysed descriptively qualitatively and quantitatively. Expired mustard seeds have fewer viable embryos than unexpired seeds. The sprout development of expired mustard seeds was slower than unexpired seeds. The fastest average germination time was in seeds soaked in 0.3% KNO3 solution for 8 hours and distilled water for 2 hours (2.53 and 2.52 days), the highest average germination percentage was in seeds soaked in 0.3% KNO3 solution for 6 hours and distilled water for 2 hours (82.5%), average hypocotyl length of the longest sprouts in seeds soaked in 0.3% KNO3 solution and 2 hours distilled water (1.62 and 1.68 cm), and average radicle length of the longest sprouts in seeds soaked in 0.3% KNO3 solution 2 hours and 10 hours distilled water (1.33 and 1.28 cm).